Design of a Novel DNA-FISH Probe for the Rapid Identification of Candida albicans in Cosmetic Products - Patrícia Branco; Margarida Nunes; Paula Pereira; Elisabete Muchagato Mauricio (Cosmetics)
Microbiological quality control in cosmetic and pharmaceutical products is crucial for consumer safety. Traditional culture-based detection methods, such as plating on selective media, are time-consuming and may lack sensitivity. Fluorescence In Situ Hybridisation (FISH), a molecular and culture-independent technique, enables rapid and precise microbial identification by targeting specific RNA or DNA sequences with fluorescent probes. In this study, a novel DNA-FISH probe was developed for the detection of Candida albicans in cosmetic formulations. The probe’s specificity was assessed in silico and experimentally using flow cytometry (flow-FISH) on C. albicans and non-target microorganisms, including Pichia kudriavzevii, commonly known as Candida krusei, Saccharomyces cerevisiae, Wickerhamomyces anomalus, Escherichia coli, and Staphylococcus aureus. The probe exhibited 98.9% hybridization efficiency with C. albicans, yielding a fluorescence intensity (FI) of 25,000 (a.u.), while non-target yeasts demonstrated minimal hybridization (4.7%, 2.3%, and 1.9% for C. krusei, S. cerevisiae, and W. anomalus, respectively) and bacteria showed negligible FI. Additionally, the probe’s applicability was evaluated in a tonic formulation, where C. albicans’ hybridization efficiency was slightly reduced to 88.4%, suggesting that formulation components may influence probe performance. Nevertheless, the probe maintained high specificity and efficiency without formamide, a toxic reagent commonly used in FISH. These findings highlight the potential of FISH probes for rapid, accurate, and safe microbial detection, offering a valuable tool for microbiological quality control in the cosmetics industry.